Transcriptional Regulation of Sorghum Stem Composition: Key Players Identified Through Co-expression Gene Network and Comparative Genomics Analyses - Hennet, Lauriane; Berger, Angélique; Trabanco, Noemi; Ricciuti, Emeline; Dufayard, Jean-François; Bocs, Stéphanie; Bastianelli, Denis; Bonnal, Laurent; Roques, Sandrine; Rossini, Laura; Luquet, Delphine; Terrier, Nancy; et al. (Frontiers in Plant Science, 2020)
Most of sorghum biomass is accumulated in stem Secondary Cell Walls (SCW). As sorghum stems are used as raw materials for various purposes such as feed, energy and fiber reinforced polymers, uncovering the genes responsible for SCW establishment is of key importance. Taking advantage of studies performed in model species, most of the structural genes contributing at the molecular level to the SCW biosynthesis in sorghum have been proposed while their regulating actors are still largely unknown. Validation of the role of several MYB and NAC transcription factors in SCW regulation in Arabidopsis and a few other species have been provided. Here we contributed to the recent efforts made in grasses to uncover the mechanisms underlying SCW establishment. We reported updated phylogenies of NAC and MYB in 9 different species and took advantage of knowledge from other species to highlight candidate regulators of SCW in sorghum. We acquired expression data during sorghum internode development and used co-expression analyses to determine groups of co-expressed genes that are likely to be involved in primary and SCW establishment. We were able to identify six groups of co-expressed genes enriched in cell wall genes including two that are linked to SCW. Gene enrichment analysis of MYB and NAC genes provided evidences that while NAC SECONDARY WALL THICKENING PROMOTING FACTOR NST genes and SECONDARY WALL-ASSOCIATED NAC DOMAIN PROTEIN genes functions seems conserved in sorghum, NAC master regulators of SCW in sorghum may be not as tissue compartmented as in Arabidopsis. We showed that for every homolog of key SCW MYB in Arabidopsis, a similar role is expected in sorghum. In addition, we unveil sorghum MYB and NAC that have not yet been identified as being involved in cell wall regulation. Even though specific validation of the MYB and NAC genes uncovered in this study is needed, we provide a network of sorghum genes involved in SCW both at the structural and regulation levels.